Challenging Neo-Colonialism in Language Testing: The Development and Impact of Indonesia's Test of Academic English Proficiency (TAEP) - Masduki (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Background: In today's globalized world, neo-colonialism exerts significant influence, particularly in political and economic spheres. This influence extends to English Language Teaching (ELT) in Indonesia, where the hegemony of a specific language test system has resulted in its overuse for multiple purposes. Methodology: This research employs a quantitative approach to design the Test of Academic English Proficiency (TAEP) for Indonesian non-native speakers, focusing on academic, business, and general settings. The four-step process includes participant selection, data collection, expert judgment, and test try-outs. Findings: The study results indicate that TAEP items are acceptable, with a high validity of .98 and reliability of .93. Four poor items require revision, while others effectively distinguish between good and poor test-takers. TAEP's content is balanced and relevant for assessing proficiency in academic, business, and general English. Conclusion: TAEP, meeting language test criteria and legally certified, has been utilized nationally and internationally, including by Bank of Indonesia, the Financial Service Authority of Indonesia (OJK), and Erasmus Mundus. This contributes to Indonesia's pursuit of independence from modern colonization. Originality: This study innovatively explores the underexamined relationship between neo-colonialism and language testing, addressing issues such as overdependence on specific tests, national spending burdens, and neglect of local linguistic and cultural contexts.